Choice overload paradox and public policy design. The case of Swedish pension system - Slawomir Czech (Institute of Economic Research (IER), 2015)
In this paper we focus on an adverse effect of extensive choice widely known as 'choice overload'. We draw on the case of Swedish funded pensions for illustration and analyze consequences of the design that allowed for maximizing the choice set. The analysis shows limitations of employing the rational choice approach to the real choice decisions biased with common psychological factors and demonstrates that government's responsibility for the privatized pension system does not end with the design. We also emphasize the need for a decent default option, which would mitigate socially harmful results of adverse behavior effects like procrastination, status quo bias or abstaining from choice. After all, privatized pension systems still belong to a sphere of public policy.
Keywords: D19; H44; H55; 330; extensive choice; cognitive limitations; market failure; choice architecture; funded pensions